Heinrich Himmler - Longerich, Peter 1955- (Oxford University Press, 2012)
"In this, the first-ever comprehensive biography of the Reichsführer-SS, leading German historian Peter Longerich puts every aspect of Himmler's life under the microscope. Masterfully interweaving the story of Himmler's personal life and political career with the wider history of the Nazi dictatorship, Longerich shows how skillfully he exploited and manipulated his disparate roles in the pursuit of his far-reaching and grandiose objectives. In the process, he illuminates the extraordinary degree to which Himmler's own personal prejudices, idiosyncrasies, and predilections made their mark on the organizations for which he was responsible--especially the SS, which in so many ways bore the characteristic hallmarks of its leader, and whose history remains incomprehensible without a detailed and intimate knowledge of its deeply sinister commander-in-chief"--Dust-jacket